High-safety distributed pole piece and lithium battery prepared from same
By introducing polymer layer, flame retardant adhesive layer and metal layer into the electrode sheet of the lithium battery, and using alumina-boehmite composite, the problem of poor safety of lithium batteries in high temperature environments is solved, and higher thermal stability and safety are achieved.
Patent Information
- Application Number
- CN202311326908.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-15
AI Technical Summary
Existing lithium batteries can easily lead to a large thermal shrinkage rate of the diaphragm in high temperature environments, resulting in contact between positive and negative electrodes, which may cause spontaneous combustion or explosion, and have poor safety.
It adopts a high-safe distributed electrode sheet design, including polymer layer, flame retardant adhesive layer, aluminum metal layer, copper metal layer, positive electrode material and negative electrode material. The alumina-boehmite composite is added to improve flame retardant performance by coating the flame retardant adhesive on both sides of the polymer film and composited with aluminum and copper metal layers.
It enhances the thermal stability of the electrode film, improves the safety of lithium batteries, delays combustion and reduces the risk of spontaneous combustion or explosion.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a high-safety distributed pole piece and a lithium battery prepared using the same. Background Art
[0002] Nowadays, with the accelerated development of information and communication, the demand for new energy is increasing. Lithium batteries have the advantages of high energy density, good cycle performance, clean and environmentally friendly, and have become the main energy source for communication electronic products. The pole piece is an important component of lithium batteries. The pole piece contains a diaphragm. When the battery is overcharged, it may cause problems such as increased internal temperature of the battery, radiation, and fire. At this time, the battery is in a high temperature environment outside, which will affect the thermal shrinkage rate of the battery diaphragm. The thermal shrinkage rate of the battery diaphragm in the prior art is large, and the battery will cause the positive and negative poles of the battery to contact each other, resulting in spontaneous combustion or explosion, etc., and the safety is poor. Therefore, the thermal stability of the diaphragm is the main factor that determines whether the lithium battery can maintain high safety performance in a high temperature environment.
[0003] In order to solve the above problems and improve the thermal stability and safety performance of the pole piece, the present invention provides a high-safety distributed pole piece and a lithium battery prepared therefrom. Summary of the invention
[0004] The object of the present invention is to provide a high-safety distributed pole piece and a lithium battery prepared therefrom, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-safety distributed pole piece and a lithium battery prepared therefrom.
[0006] A high-safety distributed pole piece, characterized in that it includes a polymer layer, a flame-retardant adhesive layer, an aluminum metal layer, a copper metal layer, a positive electrode material, and a negative electrode material; the polymer layer is a polymer film; both sides of the polymer film are coated with a flame-retardant adhesive layer, and one side of the polymer film coated with the flame-retardant adhesive layer is composited with the copper metal layer, and the other side is composited with the aluminum metal layer; the surface of the aluminum metal layer is coated with the positive electrode material, and the surface of the copper metal layer is coated with the negative electrode material.
[0007] Preferably, the aluminum metal layer is a rolled aluminum foil with a thickness of 5-20 microns; the copper metal layer is any one of an electrolytic copper foil and a rolled copper foil with a thickness of 2-20 microns.
[0008] More optimally, the polymer film is any one of polypropylene, polyethylene, and polyimide.
[0009] More optimally, the flame retardant adhesive layer is a flame retardant adhesive, and the flame retardant adhesive contains aluminum oxide and boehmite.
[0010] More optimally, the single-sided coating density of the flame retardant adhesive is 2-15 g / ㎡.
[0011] More optimally, the preparation method of the flame retardant adhesive is: stir the alumina-boehmite complex, dispersant, wetting agent, and deionized water for 5-6 hours, add xanthan gum and binder, and continue stirring for 2-3 hours to obtain the flame retardant adhesive.
[0012] Preferably, the method for preparing the alumina-boehmite composite comprises the following steps: Step 1: Take dimethyl sulfoxide, add 3-aminopropyltriethoxysilane and dibutyltin dilaurate catalyst, stir evenly, add alumina, stir for 6-7h, filter, wash and dry to obtain treated alumina; Step 2: Take isocyanate propyl triethoxysilane and toluene, add boehmite, stir evenly, heat to 75-80° C., stir for 4-5 hours, filter, wash and dry to obtain treated boehmite; Step 3: Take the treated alumina, the treated boehmite, the dibutyltin dilaurate catalyst, and deionized water, stir for 5-6 hours, filter, wash, and dry to obtain an alumina-boehmite complex.
[0013] More optimally, the preparation method of boehmite is: take aluminum hydroxide and deionized water, ball mill for 30-40 minutes, take out, react at 185-190°C for 5-6 hours, cool to 30-35°C, filter, wash, dry at 75-80°C for 10-12 hours, and crush to obtain boehmite.
[0014] A lithium battery includes a high-safety distributed pole piece.
[0015] Preferably, the preparation method of the lithium battery comprises the following steps: S1: taking a polymer film, coating both sides of the polymer film with a flame retardant adhesive, and obtaining a film coated with the flame retardant adhesive; S2: Compounding the two sides of the film coated with the flame retardant adhesive with aluminum foil and copper foil respectively to obtain an aluminum metal layer and a copper metal layer; S3: coating the positive electrode material on the surface of the aluminum metal layer, drying, and obtaining a positive electrode region; coating the negative electrode material on the surface of the copper metal layer, drying, and obtaining a negative electrode region, and obtaining a semi-finished product; S4: rolling the semi-finished product, and ultrasonically welding the pole ear in the blank area outside the positive electrode area on the aluminum metal layer, and ultrasonically welding the pole ear in the blank area outside the negative electrode area on the copper metal layer, to prepare a high-safety distributed pole piece; S5: stack the high-safety distributed pole piece and the diaphragm, ultrasonically weld the pole ears on all aluminum metal layers of the multi-layer distributed pole piece, and ultrasonically weld the pole ears on all copper metal layers, and then place them in a shell, inject dimethyl carbonate electrolyte, seal it, and obtain a lithium battery.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) The present invention adds boehmite, which absorbs a large amount of heat when decomposed by heat. The generated aluminum oxide covers the surface of the object to delay combustion and has a flame retardant effect. The present invention uses aluminum oxide with a particle size of 700nm and boehmite with a particle size of 1-3μm. The size of aluminum oxide is smaller than that of boehmite, which can fill the gaps between boehmite. Aluminum oxide with a smaller particle size has a larger specific surface area, which can increase the contact area between it and the combustion products, thereby promoting the reaction with the combustion products, further enhancing the thermal stability of the electrode film, and thus enhancing the safety of the lithium battery.
[0017] (2) The present invention uses isocyanate propyl triethoxysilane to modify boehmite so that the boehmite has isocyanate groups. A large number of hydroxyl groups on alumina can react with the isocyanate groups on the boehmite, so that the alumina and boehmite are compounded together to obtain an alumina-boehmite composite, further enhancing the thermal stability of the electrode film.
[0018] (3) The present invention adds an alumina-boehmite complex to the binder to increase the flame retardant properties of the binder, and also adds xanthan gum. The high viscosity of xanthan gum can increase the viscosity of the binder, and the xanthan gum also has good hydrophilicity. The present invention also uses 3-aminopropyltriethoxysilane to hydrophilically modify alumina. The alumina-boehmite complex has a small particle size, a large specific surface area, and a high surface energy, and is easy to agglomerate in the binder system. Therefore, the present invention uses 3-aminopropyltriethoxysilane to hydrophilically modify boehmite, so that the alumina-boehmite complex is loaded with hydrophilic groups, so that the alumina-boehmite complex is not easy to agglomerate in the hydrophilic binder, thereby improving the thermal stability of the electrode film and improving the safety of the electrode. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] There are no special restrictions on the manufacturers of all raw materials involved in the present invention, and illustratively include: PP (polypropylene) film can be provided by Dongguan Shengsi Electronics Co., Ltd.; raw rubber can be purchased from Zibo Zhongxuan Biochemical Co., Ltd.; binder: LA133, can be purchased from Zhengzhou Alpha Chemical Co., Ltd.; dispersant: BYK-LPC22092 can be purchased from BYK, Germany; wetting agent: BYK-LPC20990 can be purchased from BYK, Germany; alumina: particle size: 700nm, can be purchased from Sumitomo, Japan; aluminum hydroxide: brand: H-WF-1, can be purchased from China Aluminum Shandong Branch.
[0021] Embodiment 1: A method for preparing a lithium battery, comprising the following steps: Step 1: Preparation of boehmite: Take 15g aluminum hydroxide and 60mL deionized water and heat at a speed of 200rmin -1 The mixture was ball-milled for 35 min, taken out, reacted at 188°C for 5.5 h, cooled to 32°C, filtered, washed, dried at 78°C for 11 h, and crushed to obtain boehmite; at this time, the size of the boehmite was 1-3 μm; Step 2: Preparation of alumina-boehmite composite: Take 50 mL of dimethyl sulfoxide, add 2 mL of 3-aminopropyltriethoxysilane and 0.1 mL of dibutyltin dilaurate catalyst, stir evenly, add 5 g of alumina, stir for 6.5 h, filter, wash and dry to obtain treated alumina; Take 1 mL of isocyanatepropyltriethoxysilane and 60 mL of toluene, add 5 g of boehmite, stir evenly, heat to 78°C, stir for 4.5 hours, filter, wash and dry to obtain the treated boehmite; Take 5 g of treated alumina, 3 g of treated boehmite, 0.1 mL of dibutyltin dilaurate catalyst, and 50 mL of deionized water, stir for 5.5 h, filter, wash, and dry to obtain an alumina-boehmite composite; Step 3: Preparation of flame retardant adhesive: 500 g of alumina-boehmite composite, 16 g of BYK-LPC22092 dispersant, 16 g of BYK-LPC20990 wetting agent, and 1000 mL of deionized water were stirred for 5.5 h, 3 g of xanthan gum and 18 g of LA133 binder were added, and stirring was continued for 2.5 h to obtain a flame retardant adhesive; Step 4: Preparation of high-safety distributed pole pieces: A high molecular weight polypropylene film with a thickness of 4 µm is taken, and a flame retardant adhesive is coated on both sides of the PP film, wherein the single-side coating density of the flame retardant adhesive is 8 g / ㎡, thereby obtaining a film coated with the flame retardant adhesive; Aluminum foil with a thickness of 7µm after calendering and copper foil with a thickness of 7µm after calendering are respectively bonded to the surfaces of both sides of the film coated with the flame retardant adhesive; Add 96g of active material NMC811 to 80g of N-methylpyrrolidone (LiNi 0.8 Mn 0.1 What 0.1 O 2 ) , 2g of conductive agent carbon black and 2g of binder polyvinylidene fluoride, mix them evenly to prepare a ternary positive electrode slurry of positive electrode material, evenly coat the ternary positive electrode slurry on the surface of the aluminum metal layer, and dry; Add 95.4 g of negative electrode active material graphite powder (CAS: 7782-42-5), 2.6 g of conductive agent carbon black (CAS: 1333-86-4), 1 g of thickener sodium carboxymethyl cellulose and 1 g of binder styrene-butadiene rubber (CAS: 9003-55-8) to 90 g of deionized water, mix well to obtain negative electrode slurry, and evenly coat the negative electrode slurry on the surface of the copper metal layer and dry; Roll-pressing at 60 MPa resulted in a positive electrode material with a thickness of 120 μm and an area density of 2.0 g / dm 2 ; The thickness of the negative electrode material is 110 microns and the surface density is 2.0g / dm 2 ; Step 5: Preparation of multi-layer distributed pole pieces: Ultrasonic welding of the pole ear in the blank area outside the positive electrode area on the aluminum metal layer, and ultrasonic welding of the pole ear in the blank area outside the negative electrode area on the copper metal layer, to prepare a multi-layer distributed pole piece; Step 6: Preparation of lithium battery: The multi-layer distributed pole pieces and the diaphragm are stacked, the positive poles in all the multi-layer distributed pole pieces are ultrasonically welded together, the negative poles in all the multi-layer distributed pole pieces are ultrasonically welded together, and then placed in a shell, dimethyl carbonate electrolyte is injected, and the shell is sealed to obtain a lithium battery.
[0022] Embodiment 2: A method for preparing a lithium battery, comprising the following steps: Step 1: Preparation of boehmite: Take 15g aluminum hydroxide and 60mL deionized water and heat at a speed of 200rmin -1 The mixture was ball-milled for 30 min, taken out, reacted at 190°C for 5 h, cooled to 30°C, filtered, washed, dried at 75°C for 10 h, and crushed to obtain boehmite; at this time, the size of the boehmite was 1-3 μm; Step 2: Preparation of alumina-boehmite composite: Take 50 mL of dimethyl sulfoxide, add 2 mL of 3-aminopropyltriethoxysilane and 0.1 mL of dibutyltin dilaurate catalyst, stir evenly, add 5 g of alumina, stir for 6 hours, filter, wash and dry to obtain treated alumina; Take 1 mL of isocyanatepropyltriethoxysilane and 60 mL of toluene, add 5 g of boehmite, stir evenly, heat to 75°C, stir for 4 hours, filter, wash and dry to obtain the treated boehmite; Take 5 g of treated alumina, 3 g of treated boehmite, 0.1 mL of dibutyltin dilaurate catalyst, and 50 mL of deionized water, stir for 5 h, filter, wash, and dry to obtain an alumina-boehmite composite; Step 3: Preparation of flame retardant adhesive: 500 g of alumina-boehmite composite, 16 g of BYK-LPC22092 dispersant, 16 g of BYK-LPC20990 wetting agent, and 1000 mL of deionized water were stirred for 5 h, 3 g of xanthan gum and 18 g of LA133 binder were added, and stirring was continued for 2 h to obtain a flame retardant adhesive; Step 4: Preparation of high-safety distributed pole pieces: A high molecular weight polypropylene film with a thickness of 4 µm is taken, and a flame retardant adhesive is coated on both sides of the PP film, wherein the single-side coating density of the flame retardant adhesive is 8 g / ㎡, thereby obtaining a film coated with the flame retardant adhesive; Aluminum foil with a thickness of 7µm after calendering and copper foil with a thickness of 7µm after calendering are respectively bonded to the surfaces of both sides of the film coated with the flame retardant adhesive; Add 96g of active material NMC811 to 80g of N-methylpyrrolidone (LiNi 0.8 Mn 0.1 What 0.1 O 2 ) , 2g of conductive agent carbon black and 2g of binder polyvinylidene fluoride, mix them evenly to prepare a ternary positive electrode slurry of positive electrode material, evenly coat the ternary positive electrode slurry on the surface of the aluminum metal layer, and dry; Add 95.4 g of negative electrode active material graphite powder (CAS: 7782-42-5), 2.6 g of conductive agent carbon black (CAS: 1333-86-4), 1 g of thickener sodium carboxymethyl cellulose and 1 g of binder styrene-butadiene rubber (CAS: 9003-55-8) to 90 g of deionized water, mix well to obtain negative electrode slurry, and evenly coat the negative electrode slurry on the surface of the copper metal layer and dry; Roll-pressing at 60 MPa resulted in a positive electrode material with a thickness of 120 μm and an area density of 2.0 g / dm 2; The thickness of the negative electrode material is 110 microns and the surface density is 2.0g / dm 2 ; Step 5: Preparation of multi-layer distributed pole pieces: Ultrasonic welding of the pole ear in the blank area outside the positive electrode area on the aluminum metal layer, and ultrasonic welding of the pole ear in the blank area outside the negative electrode area on the copper metal layer, to prepare a multi-layer distributed pole piece; Step 6: Preparation of lithium battery: The multi-layer distributed pole pieces and the diaphragm are stacked, the positive poles in all the multi-layer distributed pole pieces are ultrasonically welded together, the negative poles in all the multi-layer distributed pole pieces are ultrasonically welded together, and then placed in a shell, dimethyl carbonate electrolyte is injected, and the shell is sealed to obtain a lithium battery.
[0023] Embodiment 3: A method for preparing a lithium battery, comprising the following steps: Step 1: Preparation of boehmite: Take 15g aluminum hydroxide and 60mL deionized water and heat at a speed of 200rmin -1 The mixture was ball-milled for 40 min, taken out, reacted at 190°C for 6 h, cooled to 35°C, filtered, washed, dried at 80°C for 12 h, and crushed to obtain boehmite; at this time, the size of the boehmite was 3 μm; Step 2: Preparation of alumina-boehmite composite: Take 50 mL of dimethyl sulfoxide, add 2 mL of 3-aminopropyltriethoxysilane and 0.1 mL of dibutyltin dilaurate catalyst, stir evenly, add 5 g of alumina, stir for 7 hours, filter, wash and dry to obtain treated alumina; Take 1 mL of isocyanatepropyltriethoxysilane and 60 mL of toluene, add 5 g of boehmite, stir evenly, heat to 80°C, stir for 5 hours, filter, wash and dry to obtain the treated boehmite; Take 5 g of the treated alumina, 3 g of the treated boehmite, 0.1 mL of dibutyltin dilaurate catalyst, and 50 mL of deionized water, stir for 6 h, filter, wash, and dry to obtain an alumina-boehmite composite; Step 3: Preparation of flame retardant adhesive: 500 g of alumina-boehmite composite, 16 g of BYK-LPC22092 dispersant, 16 g of BYK-LPC20990 wetting agent, and 1000 mL of deionized water were stirred for 6 h, 3 g of xanthan gum and 18 g of LA133 binder were added, and stirring was continued for 3 h to obtain a flame retardant adhesive; Step 4: Preparation of high-safety distributed pole pieces: A high molecular weight polypropylene film with a thickness of 4 µm is taken, and a flame retardant adhesive is coated on both sides of the PP film, wherein the single-side coating density of the flame retardant adhesive is 8 g / ㎡, thereby obtaining a film coated with the flame retardant adhesive; Aluminum foil with a thickness of 7µm after calendering and copper foil with a thickness of 7µm after calendering are respectively bonded to the surfaces of both sides of the film coated with the flame retardant adhesive; Add 96g of active material NMC811 to 80g of N-methylpyrrolidone (LiNi 0.8 Mn 0.1 What 0.1 O 2 ) , 2g of conductive agent carbon black and 2g of binder polyvinylidene fluoride, mix them evenly to prepare a ternary positive electrode slurry of positive electrode material, evenly coat the ternary positive electrode slurry on the surface of the aluminum metal layer, and dry; Add 95.4 g of negative electrode active material graphite powder (CAS: 7782-42-5), 2.6 g of conductive agent carbon black (CAS: 1333-86-4), 1 g of thickener sodium carboxymethyl cellulose and 1 g of binder styrene-butadiene rubber (CAS: 9003-55-8) to 90 g of deionized water, mix well to obtain negative electrode slurry, and evenly coat the negative electrode slurry on the surface of the copper metal layer and dry; Roll-pressing at 60 MPa resulted in a positive electrode material with a thickness of 120 μm and an area density of 2.0 g / dm 2 ; The thickness of the negative electrode material is 110 microns and the surface density is 2.0g / dm 2 ; Step 5: Preparation of multi-layer distributed pole pieces: Ultrasonic welding of the pole ear in the blank area outside the positive electrode area on the aluminum metal layer, and ultrasonic welding of the pole ear in the blank area outside the negative electrode area on the copper metal layer, to prepare a multi-layer distributed pole piece; Step 6: Preparation of lithium battery: The multi-layer distributed pole pieces and the diaphragm are stacked, the positive poles in all the multi-layer distributed pole pieces are ultrasonically welded together, the negative poles in all the multi-layer distributed pole pieces are ultrasonically welded together, and then placed in a shell, dimethyl carbonate electrolyte is injected, and the shell is sealed to obtain a lithium battery.
[0024] Comparative Example 1: 3-aminopropyltriethoxysilane is not used to modify the aluminum oxide, and the rest is the same as Example 1: Step 1: Preparation of boehmite: Take 15g aluminum hydroxide and 60mL deionized water and heat at a speed of 200rmin -1The mixture was ball-milled for 35 min, taken out, reacted at 188°C for 5.5 h, cooled to 32°C, filtered, washed, dried at 78°C for 11 h, and crushed to obtain boehmite; at this time, the size of the boehmite was 1-3 μm; Step 2: Preparation of alumina-boehmite composite: Take 1 mL of isocyanatepropyltriethoxysilane and 60 mL of toluene, add 5 g of boehmite, stir evenly, heat to 78°C, stir for 4.5 hours, filter, wash and dry to obtain the treated boehmite; Take 5 g of alumina, 3 g of treated boehmite, 0.1 mL of dibutyltin dilaurate catalyst, and 50 mL of deionized water, stir for 5.5 h, filter, wash, and dry to obtain an alumina-boehmite composite; Step 3: Preparation of flame retardant adhesive: 500 g of alumina-boehmite composite, 16 g of BYK-LPC22092 dispersant, 16 g of BYK-LPC20990 wetting agent, and 1000 mL of deionized water were stirred for 5.5 h, 3 g of xanthan gum and 18 g of LA133 binder were added, and stirring was continued for 2.5 h to obtain a flame retardant adhesive; Step 4: Preparation of high-safety distributed pole pieces: A high molecular weight polypropylene film with a thickness of 4 µm is taken, and a flame retardant adhesive is coated on both sides of the PP film, wherein the single-side coating density of the flame retardant adhesive is 8 g / ㎡, thereby obtaining a film coated with the flame retardant adhesive; Aluminum foil with a thickness of 7µm after calendering and copper foil with a thickness of 7µm after calendering are respectively bonded to the surfaces of both sides of the film coated with the flame retardant adhesive; Add 96g of active material NMC811 to 80g of N-methylpyrrolidone (LiNi 0.8 Mn 0.1 What 0.1 O 2 ) , 2g of conductive agent carbon black and 2g of binder polyvinylidene fluoride, mix them evenly to prepare a ternary positive electrode slurry of positive electrode material, evenly coat the ternary positive electrode slurry on the surface of the aluminum metal layer, and dry; Add 95.4 g of negative electrode active material graphite powder (CAS: 7782-42-5), 2.6 g of conductive agent carbon black (CAS: 1333-86-4), 1 g of thickener sodium carboxymethyl cellulose and 1 g of binder styrene-butadiene rubber (CAS: 9003-55-8) to 90 g of deionized water, mix well to obtain negative electrode slurry, and evenly coat the negative electrode slurry on the surface of the copper metal layer and dry; Roll-pressing at 60 MPa resulted in a positive electrode material with a thickness of 120 μm and an area density of 2.0 g / dm 2 ; The thickness of the negative electrode material is 110 microns and the surface density is 2.0g / dm 2 ; Step 5: Preparation of multi-layer distributed pole pieces: Ultrasonic welding of the pole ear in the blank area outside the positive electrode area on the aluminum metal layer, and ultrasonic welding of the pole ear in the blank area outside the negative electrode area on the copper metal layer, to prepare a multi-layer distributed pole piece; Step 6: Preparation of lithium battery: The multi-layer distributed pole pieces and the diaphragm are stacked, the positive poles in all the multi-layer distributed pole pieces are ultrasonically welded together, the negative poles in all the multi-layer distributed pole pieces are ultrasonically welded together, and then placed in a shell, dimethyl carbonate electrolyte is injected, and the shell is sealed to obtain a lithium battery.
[0025] Comparative Example 2: The boehmite is not modified by using isocyanate propyl triethoxysilane, and the rest is the same as Example 1: Step 1: Preparation of boehmite: Take 15g aluminum hydroxide and 60mL deionized water and heat at a speed of 200rmin -1 The mixture was ball-milled for 35 min, taken out, reacted at 188°C for 5.5 h, cooled to 32°C, filtered, washed, dried at 78°C for 11 h, and crushed to obtain boehmite; at this time, the size of the boehmite was 1-3 μm; Step 2: Preparation of alumina-boehmite composite: Take 50 mL of dimethyl sulfoxide, add 2 mL of 3-aminopropyltriethoxysilane and 0.1 mL of dibutyltin dilaurate catalyst, stir evenly, add 5 g of alumina, stir for 6.5 h, filter, wash and dry to obtain treated alumina; Take 5 g of the treated alumina, 3 g of boehmite, 0.1 mL of dibutyltin dilaurate catalyst, and 50 mL of deionized water, stir for 5.5 h, filter, wash, and dry to obtain an alumina-boehmite composite; Step 3: Preparation of flame retardant adhesive: 500 g of alumina-boehmite composite, 16 g of BYK-LPC22092 dispersant, 16 g of BYK-LPC20990 wetting agent, and 1000 mL of deionized water were stirred for 5.5 h, 3 g of xanthan gum and 18 g of LA133 binder were added, and stirring was continued for 2.5 h to obtain a flame retardant adhesive; Step 4: Preparation of high-safety distributed pole pieces: A high molecular weight polypropylene film with a thickness of 4 µm is taken, and a flame retardant adhesive is coated on both sides of the PP film, wherein the single-side coating density of the flame retardant adhesive is 8 g / ㎡, thereby obtaining a film coated with the flame retardant adhesive; Aluminum foil with a thickness of 7µm after calendering and copper foil with a thickness of 7µm after calendering are respectively bonded to the surfaces of both sides of the film coated with the flame retardant adhesive; Add 96g of active material NMC811 to 80g of N-methylpyrrolidone (LiNi 0.8 Mn 0.1 What 0.1 O 2 ) , 2g of conductive agent carbon black and 2g of binder polyvinylidene fluoride, mix them evenly to prepare a ternary positive electrode slurry of positive electrode material, evenly coat the ternary positive electrode slurry on the surface of the aluminum metal layer, and dry; Add 95.4 g of negative electrode active material graphite powder (CAS: 7782-42-5), 2.6 g of conductive agent carbon black (CAS: 1333-86-4), 1 g of thickener sodium carboxymethyl cellulose and 1 g of binder styrene-butadiene rubber (CAS: 9003-55-8) to 90 g of deionized water, mix well to obtain negative electrode slurry, and evenly coat the negative electrode slurry on the surface of the copper metal layer and dry; Roll-pressing at 60 MPa resulted in a positive electrode material with a thickness of 120 μm and an area density of 2.0 g / dm 2 ; The thickness of the negative electrode material is 110 microns and the surface density is 2.0g / dm 2 ; Step 5: Preparation of multi-layer distributed pole pieces: Ultrasonic welding of the pole ear in the blank area outside the positive electrode area on the aluminum metal layer, and ultrasonic welding of the pole ear in the blank area outside the negative electrode area on the copper metal layer, to prepare a multi-layer distributed pole piece; Step 6: Preparation of lithium battery: The multi-layer distributed pole pieces and the diaphragm are stacked, the positive poles in all the multi-layer distributed pole pieces are ultrasonically welded together, the negative poles in all the multi-layer distributed pole pieces are ultrasonically welded together, and then placed in a shell, dimethyl carbonate electrolyte is injected, and the shell is sealed to obtain a lithium battery.
[0026] Comparative Example 3: No xanthan gum was added, and the rest was the same as Example 1: Step 1: Preparation of boehmite: Take 15g aluminum hydroxide and 60mL deionized water and heat at a speed of 200rmin -1 The mixture was ball-milled for 35 min, taken out, reacted at 188°C for 5.5 h, cooled to 32°C, filtered, washed, dried at 78°C for 11 h, and crushed to obtain boehmite; at this time, the size of the boehmite was 1-3 μm; Step 2: Preparation of alumina-boehmite composite: Take 50 mL of dimethyl sulfoxide, add 2 mL of 3-aminopropyltriethoxysilane and 0.1 mL of dibutyltin dilaurate catalyst, stir evenly, add 5 g of alumina, stir for 6.5 h, filter, wash and dry to obtain treated alumina; Take 1 mL of isocyanatepropyltriethoxysilane and 60 mL of toluene, add 5 g of boehmite, stir evenly, heat to 78°C, stir for 4.5 hours, filter, wash and dry to obtain the treated boehmite; Take 5 g of treated alumina, 3 g of treated boehmite, 0.1 mL of dibutyltin dilaurate catalyst, and 50 mL of deionized water, stir for 5.5 h, filter, wash, and dry to obtain an alumina-boehmite composite; Step 3: Preparation of flame retardant adhesive: 500 g of alumina-boehmite composite, 16 g of BYK-LPC22092 dispersant, 16 g of BYK-LPC20990 wetting agent, and 1000 mL of deionized water were stirred for 5.5 h, 25 g of LA133 binder was added, and stirring was continued for 2.5 h to obtain a flame retardant adhesive; Step 4: Preparation of high-safety distributed pole pieces: A high molecular weight polypropylene film with a thickness of 4 µm is taken, and a flame retardant adhesive is coated on both sides of the PP film, wherein the single-side coating density of the flame retardant adhesive is 8 g / ㎡, thereby obtaining a film coated with the flame retardant adhesive; Aluminum foil with a thickness of 7µm after calendering and copper foil with a thickness of 7µm after calendering are respectively bonded to the surfaces of both sides of the film coated with the flame retardant adhesive; Add 96g of active material NMC811 to 80g of N-methylpyrrolidone (LiNi 0.8 Mn 0.1 What 0.1 O 2 ) , 2g of conductive agent carbon black and 2g of binder polyvinylidene fluoride, mix them evenly to prepare a ternary positive electrode slurry of positive electrode material, evenly coat the ternary positive electrode slurry on the surface of the aluminum metal layer, and dry; Add 95.4 g of negative electrode active material graphite powder (CAS: 7782-42-5), 2.6 g of conductive agent carbon black (CAS: 1333-86-4), 1 g of thickener sodium carboxymethyl cellulose and 1 g of binder styrene-butadiene rubber (CAS: 9003-55-8) to 90 g of deionized water, mix well to obtain negative electrode slurry, and evenly coat the negative electrode slurry on the surface of the copper metal layer and dry; Roll-pressing at 60 MPa resulted in a positive electrode material with a thickness of 120 μm and an area density of 2.0 g / dm 2; The thickness of the negative electrode material is 110 microns and the surface density is 2.0g / dm 2 ; Step 5: Preparation of multi-layer distributed pole pieces: Ultrasonic welding of the pole ear in the blank area outside the positive electrode area on the aluminum metal layer, and ultrasonic welding of the pole ear in the blank area outside the negative electrode area on the copper metal layer, to prepare a multi-layer distributed pole piece; Step 6: Preparation of lithium battery: The multi-layer distributed pole pieces and the diaphragm are stacked, the positive poles in all the multi-layer distributed pole pieces are ultrasonically welded together, the negative poles in all the multi-layer distributed pole pieces are ultrasonically welded together, and then placed in a shell, dimethyl carbonate electrolyte is injected, and the shell is sealed to obtain a lithium battery.
[0027] experiment: Take the films coated with flame retardant adhesive prepared in Examples 1 to 3 and Comparative Examples 1 to 3, and place the films at 80°C and 150°C for 30 minutes, respectively, and test the thermal shrinkage of the films to characterize the thermal stability of the films. After the lithium battery prepared by the present invention is fully charged, put it into a temperature box, and raise the temperature from room temperature to 150°C at a rate of 5°C / min, and keep this temperature for 30 minutes before stopping heating and observing for 1 hour.
[0028]
[0029] Conclusion: In Comparative Example 1, 3-aminopropyltriethoxysilane is not added to modify the alumina, and the alumina-boehmite complex is easy to agglomerate in the binder system, the composite performance of alumina and boehmite is poor, the alumina loaded on the boehmite is small, the thermal shrinkage of the film is 7.2%, the thermal stability of the film is poor, and the safety of the pole piece is deteriorated. In Comparative Example 2, isocyanatepropyltriethoxysilane is not used to modify the boehmite, the alumina loaded on the boehmite is small, the thermal shrinkage of the film is 5.2%, and the thermal stability of the film decreases. In Comparative Example 3, xanthan gum is not added, and the alumina-boehmite complex is easy to agglomerate in the flame retardant binder, which affects the thermal stability of the film. The lithium battery prepared by Examples 1 to 3 of the present invention has better flame retardancy and will not catch fire until 30 minutes later.
[0030] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-safety distributed pole piece, characterized in that: It includes a polymer layer, a flame retardant adhesive layer, an aluminum metal layer, a copper metal layer, a positive electrode material, and a negative electrode material; the polymer layer is a polymer film; both sides of the polymer film are coated with a flame retardant adhesive layer, and one side of the polymer film coated with the flame retardant adhesive layer is composited with the copper metal layer, and the other side is composited with the aluminum metal layer; the surface of the aluminum metal layer is coated with the positive electrode material, and the surface of the copper metal layer is coated with the negative electrode material.
2. A high-safety distributed pole piece according to claim 1, characterized in that: The aluminum metal layer is a rolled aluminum foil with a thickness of 5-20 microns; the copper metal layer is any one of an electrolytic copper foil and a rolled copper foil with a thickness of 2-20 microns.
3. A high-safety distributed pole piece according to claim 1, characterized in that: The polymer film is any one of polypropylene, polyethylene and polyimide.
4. A high-safety distributed pole piece according to claim 1, characterized in that: The flame retardant adhesive layer is a flame retardant adhesive, and the flame retardant adhesive contains aluminum oxide and boehmite.
5. A high-safety distributed pole piece according to claim 4, characterized in that: The single-side coating density of the flame retardant adhesive is 2-15 g / ㎡.
6. A high-safety distributed pole piece according to claim 5, characterized in that: The preparation method of the flame retardant adhesive comprises: stirring an alumina-boehmite complex, a dispersant, a wetting agent and deionized water for 5-6 hours, adding xanthan gum and a binder, and continuing stirring for 2-3 hours to obtain the flame retardant adhesive.
7. A high-safety distributed pole piece according to claim 6, characterized in that: The preparation method of the alumina-boehmite composite comprises the following steps: Step 1: Take dimethyl sulfoxide, add 3-aminopropyltriethoxysilane and dibutyltin dilaurate catalyst, stir evenly, add alumina, stir for 6-7h, filter, wash and dry to obtain treated alumina; Step 2: Take isocyanate propyl triethoxysilane and toluene, add boehmite, stir evenly, heat to 75-80° C., stir for 4-5 hours, filter, wash and dry to obtain treated boehmite; Step 3: Take the treated alumina, the treated boehmite, the dibutyltin dilaurate catalyst, and deionized water, stir for 5-6 hours, filter, wash, and dry to obtain an alumina-boehmite complex.
8. A high-safety distributed pole piece according to claim 7, characterized in that: The preparation method of boehmite is as follows: aluminum hydroxide and deionized water are taken, ball-milled for 30-40 minutes, taken out, reacted at 185-190° C. for 5-6 hours, cooled to 30-35° C., filtered, washed, dried at 75-80° C. for 10-12 hours, and crushed to obtain boehmite.
9. A lithium battery, characterized in that: Including the high-security distributed pole piece as described in any one of claims 1-8.
10. A lithium battery according to claim 9, characterized in that: The preparation method of the lithium battery is as follows: The following steps are involved: S1: taking a polymer film, coating both sides of the polymer film with a flame retardant adhesive, and obtaining a film coated with the flame retardant adhesive; S2: Compounding the two sides of the film coated with the flame retardant adhesive with aluminum foil and copper foil respectively to obtain an aluminum metal layer and a copper metal layer; S3: coating the positive electrode material on the surface of the aluminum metal layer, drying, and obtaining a positive electrode region; coating the negative electrode material on the surface of the copper metal layer, drying, and obtaining a negative electrode region, and obtaining a semi-finished product; S4: rolling the semi-finished product, and ultrasonically welding the pole ear in the blank area outside the positive electrode area on the aluminum metal layer, and ultrasonically welding the pole ear in the blank area outside the negative electrode area on the copper metal layer, to prepare a high-safety distributed pole piece; S4: stack the high-safety distributed pole piece and the diaphragm, ultrasonically weld the pole ears on all aluminum metal layers of the multi-layer distributed pole piece, and ultrasonically weld the pole ears on all copper metal layers, and then place them in a shell, inject dimethyl carbonate electrolyte, seal it, and obtain a lithium battery.